Toxicity of different permeable and non-permeable cryoprotectants on turbot embryos (Scophthalmus maximus) - Cabrita, Elsa; Robles, Vanesa; Chereguini-Fernández-Maquieira; María del Olvido; Ruiz-Villarreal, Manuel; Herráez, Paz (2002)
Sí